Measuring automatic value orientations: The Achievement–Benevolence Implicit Association Test. (19th November 2017) - Dentale, Francesco; Vecchione, Michele; Gebauer, Jochen E.; Barbaranelli, Claudio
Abstract : The construct and criterion validity of an Implicit Association Test designed to rate the importance ascribed to Achievement–Benevolence oriented goals (AB‐IAT) according to Schwartz's model were investigated. In a first study ( N  =   113), the AB‐IAT and three other value‐IATs (Power–Universalism, Security–Self‐direction, and Tradition–Stimulation) were administered along with the corresponding self‐report scales. The AB‐IAT showed the following: (1) an adequate internal consistency; (2) a small correlation and a different pattern of means with respect to the corresponding self‐report scale; (3) a pattern of correlations with the other value‐IATs that is consistent with Schwartz's model. In a second study ( N  =   99), results showed that (1) in contrast to self‐report measures of values, the AB‐IAT appeared unrelated to social desirability; (2) the AB‐IAT was significantly correlated with an actual behaviour expressing Benevolence values; (3) in accordance with a double dissociation pattern of prediction, implicit and explicit values are best predictors of actual and self‐rated behaviours, respectively. Overall, results of the studies support the construct and criterion validity of the AB‐IAT. Moreover, they provide a first support for the generalizability of Schwartz's model in the realm of implicit social cognition, and for the applicability of dual‐process models in value research.